ナンキョク オオガタ セツジョウシャ (SM100S) ノ カイハツ V. セイノウ シケン - 斉藤, 満; サイトウ, ミツル; 関, 剛; セキ, ツヨシ; 細谷, 昌之; ホソヤ, マサユキ; Saito, Mitsuru; Seki, Tsuyoshi; Hosoya, Masayuki (1992)
P(論文) この報告は, 南極氷床ドーム深層掘削計画に使用するため, 新たに開発した大型雪上車の基本性能及び総合性能の試験結果について述べたものである。試験した結果, この雪上車は, 設定した性能及びシステムデザインのねらいをおおむね満足しているが, 構造の一部に不具合部分があることも認められた。試験は, 再現性を有し類似車両と性能の比較ができるコンクリート舗装路及び南極の積雪の硬さを模擬して造った転圧雪路で行った。 This paper describes the results of the fundamental and the general performance tests for a newly developed snow vehicle, which will be used for the deep ice coring project at Dome Fuji, East Antarctica. The result of the tests showed that the vehicle generally satisfied the expected performance and the purpose of the systems design, but was partially unsatisfactory in its structure. The tests were carried out on the concrete pavement where its reproducibility is capable of comparing with the performance of similar vehicles and on the compacted snow surface which has the simulated hardness of the Antarctic snow. departmental bulletin paper